Resin composition, nonwoven fabric and method for producing the same, fiber product, separator for power storage element, secondary battery, and electric double layer capacitor
Patent Information
- Application Number
- CN202180067308.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-11-04
- Filing Date
- 2021-10-27
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2041-10-27
AI Technical Summary
[0021]根据本发明,可抑制纺丝过程中的珠粒的产生而获得稳定的直径的丝。特别是在电场纺丝过程中,不妨碍由纺丝过程中的电荷排斥引起的树脂液的分裂,从而可获得无液滴物的堆积的不织布。另外,根据本发明,可获得强度优异的耐热不织布。
Smart Images

Figure QLYQS_1 
Figure QLYQS_2 
Figure QLYQS_3
Abstract
Description
Technical Field
[0001] This invention relates to a resin composition for forming nonwoven fabrics by electric field spinning, nonwoven fabrics and their manufacturing methods, fiber articles using the same, separators for energy storage elements, secondary batteries, and double-layer capacitors. Background Technology
[0002] In recent years, electronic devices have demanded lower dielectric constants, thus requiring porous, heat-resistant materials. Nonwoven fabrics with heat resistance capable of withstanding soldering processes are a strong candidate for this purpose. Furthermore, heat-resistant nonwoven fabrics, through metallization, can be used in lightweight and excellent electromagnetic wave shielding materials, heat-resistant bag filters for removing dust from combustion gases emitted from factories, gas separation membranes or water separation membranes, and separators for lithium-ion batteries or double-layer capacitors. In these applications, metallized heat-resistant nonwoven fabrics have attracted significant attention due to their excellent ion permeability, high mechanical strength, and heat resistance.
[0003] In addition, in aircraft applications, there is an increasing demand for heat-insulating and sound-absorbing materials that are highly reliable and have many pores in high and low temperature environments.
[0004] As a method for obtaining such nonwoven fabric, Patent Document 1 discloses a method for manufacturing a polyimide composition having a specific structure suitable for electric field spinning and a nonwoven fabric using the polyimide composition, which is used as a bag filter or a combustion exhaust filter for use at high temperatures.
[0005] Patent document 2 discloses a method for obtaining polyimide fibers by spraying a polyimide solution from a nozzle and blowing a high-speed airflow that intersects with it, and is applicable to heat-resistant bag filters, heat-insulating and sound-absorbing materials, heat-resistant clothing, etc. that use the polyimide fibers.
[0006] Patent document 3 discloses a separator for lithium-ion secondary batteries that uses a resin solution formed by reacting polyamic acid with an alkoxysilane containing an epoxy group. By modifying the polyamic acid with silane, the adhesion of the coating is improved. Furthermore, in the spinning process, a gas stream heated to 50°C to 350°C is blown into the solution ejected from the spinning die, thereby simultaneously carrying out imidization and sol-gel reactions while recovering the filament.
[0007] Patent document 4 discloses nonwoven fabrics and separators using polyamides, polyimides, polyamide-imides resins with alkyl or fluoroalkyl groups bonded to the polymer ends and solutions thereof.
[0008] Existing technical documents
[0009] Patent documents
[0010] Patent Document 1: Japanese Patent Application Publication No. 2011-132611
[0011] Patent Document 2: International Publication No. 2009 / 054349
[0012] Patent Document 3: Japanese Patent Application Publication No. 2012-251287
[0013] Patent Document 4: International Publication No. 2019 / 009037 Summary of the Invention
[0014] The problem that the invention aims to solve
[0015] However, the compositions disclosed in these patent documents have a problem with poor stability during spinning. For example, sometimes nodular defects called beads, where the fiber diameter suddenly increases, are formed in the fiber, or the charge repulsion during spinning becomes unstable and the fiber loses its shape, thus accumulating as round droplets on the substrate. The reduction in the strength of the nonwoven fabric due to such problems has become a concern.
[0016] One object of the present invention is to provide a resin composition suitable for spinning, particularly electrospinning. Another object is to provide a heat-resistant nonwoven fabric with excellent strength and a method for manufacturing the same.
[0017] Technical means to solve the problem
[0018] The present invention is a resin composition for forming nonwoven fabric by electric field spinning, the resin composition comprising: (a) at least one heat-resistant resin or a precursor thereof selected from the group consisting of heat-resistant resins containing nitrogen atoms and heat-resistant resins having a group selected from the group consisting of ether, ketone, sulfone and thioether groups in the main chain; (b) a solvent; and (c) a surfactant having a fluoroalkyl group.
[0019] In addition, the present invention is a nonwoven fabric comprising: (a) at least one heat-resistant resin or a precursor thereof selected from the group consisting of heat-resistant resins containing nitrogen atoms and heat-resistant resins having a group selected from the group consisting of ether groups, ketone groups, sulfone groups and thioether groups in the main chain; and (c) a surfactant having a fluoroalkyl group.
[0020] The effects of the invention
[0021] According to the present invention, the formation of beads during the spinning process can be suppressed to obtain filaments with a stable diameter. In particular, during electric field spinning, the splitting of the resin liquid caused by charge repulsion during spinning is not hindered, thereby obtaining a nonwoven fabric without droplet accumulation. Furthermore, according to the present invention, a heat-resistant nonwoven fabric with excellent strength can be obtained. Detailed Implementation
[0022] Hereinafter, preferred embodiments of the resin composition, nonwoven fabric, method for manufacturing the nonwoven fabric, fiber product, separator, secondary battery, and double-layer capacitor of the present invention will be described in detail. However, the present invention is not limited to these embodiments.
[0023] <Resin Composition>
[0024] The resin composition of the embodiments of the present invention can be used
[0025] i) Heat-resistant resins containing nitrogen atoms,
[0026] ii) Heat-resistant resins having groups selected from the group consisting of ether, ketone, sulfone, and thioether groups in their main chain;
[0027] iii) The precursor of the heat-resistant resin described in i),
[0028] iv) The heat-resistant resin precursor of ii)
[0029] One or more of the resins are components of (a).
[0030] In addition, the resin composition of the present invention, besides containing the resin of component (a), further contains at least (b) a solvent and (c) a surfactant having a fluoroalkyl group.
[0031] Furthermore, the term "heat-resistant resin" as used in this invention refers to a resin with a 5% weight reduction temperature of 200°C or higher. Additionally, the term "precursor to heat-resistant resin" refers to a substance that provides heat-resistant resin not through addition reactions but through heat treatment or chemical treatment such as crosslinking, thermal ring-closure, or chemical ring-closure.
[0032] In addition, the so-called 5% weight reduction temperature refers to the temperature at which the resin is heated to 150°C under a nitrogen flow at a heating rate of 10°C / min and the adsorbed water is removed, then temporarily cooled to room temperature and the weight W1 is measured, and when the resin is heated again at a heating rate of 10°C / min, the weight W2 of the resin during the heating process becomes W2 / W1 = 0.95.
[0033] (a-1) Heat-resistant resin containing nitrogen atoms
[0034] The so-called heat-resistant resin containing nitrogen atoms refers to a resin that has nitrogen-containing groups such as amide groups or urea groups, or nitrogen-containing heterocycles such as imide rings or oxazole rings in the repeating structure of the polymer, and has a temperature of 200°C or higher when the weight decreases by 5%.
[0035] Examples of heat-resistant resins containing nitrogen atoms include: polyimide, polyamide, polyurea, polyamide-imide, polyazole (polybenzimidazole, polybenzoxazole, polybenzothiazole), etc.
[0036] As a heat-resistant resin containing nitrogen atoms, it is particularly preferred to be a resin having a structure represented by at least one of the following general formulas (1) to (5).
[0037] [Chemistry 1]
[0038]
[0039] In general formula (1), R 1 R represents a divalent group with 2 to 50 carbon atoms. 2 This represents a tetravalent base with 4 to 50 carbon atoms. m1 represents an integer from 1 to 10000.
[0040] [Chemistry 2]
[0041]
[0042] In general formula (2), R 3 R represents a divalent group with 2 to 50 carbon atoms. 4 This represents a trivalent group with 4 to 50 carbon atoms. m2 represents an integer from 1 to 10000.
[0043] [Chemistry 3]
[0044]
[0045] In general formula (3), R 5 R represents a divalent group with 2 to 50 carbon atoms. 6 This represents a divalent group with 2 to 50 carbon atoms. m3 represents an integer from 1 to 10000.
[0046] [Chemistry 4]
[0047]
[0048] In general formula (4), R 7 R represents a divalent group with 2 to 50 carbon atoms. 8 This represents a divalent group with 2 to 50 carbon atoms. m4 represents an integer from 1 to 10000.
[0049] [Chemistry 5]
[0050]
[0051] In general formula (5), R 9 R represents a divalent group with 2 to 50 carbon atoms. 10It represents a tetravalent group with 4 to 50 carbon atoms. X represents a divalent group selected from -O-, -S-, -NH- and -C(=O)O-.
[0052] m5 represents an integer from 1 to 10000.
[0053] Furthermore, R 1 ~R 10 Typically, these are residues of aliphatic hydrocarbons, aromatic hydrocarbons, and nitrogen-containing aromatic hydrocarbons. In addition, they also include those formed by linkages such as single bonds, ether bonds, thioether bonds, ester bonds, ketone bonds, and sulfone bonds, or those formed by substitution of a portion of hydrogen with monovalent functional groups such as alkyl, haloalkyl, oxyalkyl, oxyaryl, nitro, cyano, and halogen.
[0054] The structure represented by general formula (1) is a structural unit of polyimide. In general formula (1), R 1This indicates a diamine residue. Examples of amine components that provide diamine residues include: carboxyl-containing diamines such as 3,5-diaminobenzoic acid and 3-carboxyl-4,4'-diaminodiphenyl ether; sulfonic acid-containing diamines such as 3-sulfonic acid-4,4'-diaminodiphenyl ether; bis(3-amino-4-hydroxyphenyl)hexafluoropropane; bis(3-amino-4-hydroxyphenyl)sulfone; bis(3-amino-4-hydroxyphenyl)propane; bis(3-amino-4-hydroxyphenyl)methane; bis(3-amino-4-hydroxyphenyl) ether; bis(3-amino-4-hydroxy)biphenyl; bis(3-amino-4-hydroxyphenyl)fluorene; bis(4-amino- 3-Hydroxyphenyl)hexafluoropropane, bis(4-amino-3-hydroxyphenyl)sulfone, bis(4-amino-3-hydroxyphenyl)propane, bis(4-amino-3-hydroxyphenyl)methane, bis(4-amino-3-hydroxyphenyl) ether, bis(4-amino-3-hydroxy)biphenyl, bis(4-amino-3-hydroxyphenyl)fluorene and other hydroxyl-containing diamines, or amines formed by substituting these hydroxyl groups with thiol, amino, or carboxyl groups, 3,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylmethane, 3,4'-diaminodiphenylmethane Phenyl sulfone, 4,4'-diaminodiphenyl sulfone, 3,4'-diaminodiphenyl sulfide, 4,4'-diaminodiphenyl sulfide, 1,4-bis(4-aminophenoxy)benzene, m-phenylenediamine, p-phenylenediamine, 2,4-diaminotoluene, 2,6-diaminotoluene, 1,5-naphthyldiamine, 2,6-naphthyldiamine, bis(4-aminophenoxyphenyl)sulfone, bis(3-aminophenoxyphenyl)sulfone, bis(4-aminophenoxy)biphenyl, bis{4-(4-aminophenoxy)phenyl} ether, 1,4-bis(4-aminophenoxy)benzene, 2,2'-dimethyl-4,4'-diamino Biphenyl, 2,2'-diethyl-4,4'-diaminobiphenyl, 3,3'-dimethyl-4,4'-diaminobiphenyl, 3,3'-diethyl-4,4'-diaminobiphenyl, 2,2',3,3'-tetramethyl-4,4'-diaminobiphenyl, 3,3',4,4'-tetramethyl-4,4'-diaminobiphenyl, 2,2'-di(trifluoromethyl)-4,4'-diaminobiphenyl, or compounds in which a portion of the hydrogen atom of these aromatic rings is substituted with an alkyl or halogen atom, or aliphatic diamines such as cyclohexyldiamine and methylene dicyclohexylamine, but not limited to these. These amines can be used alone or in combination of two or more.
[0055] In general formula (1), R 2This indicates a tetracarboxylic acid residue. Examples of acidic components providing tetracarboxylic acid residues include: pyromellitic acid, 3,3',4,4'-biphenyltetracarboxylic acid, 2,3,3',4'-biphenyltetracarboxylic acid, 2,2',3,3'-biphenyltetracarboxylic acid, 3,3',4,4'-benzophenonetetracarboxylic acid, 2,2',3,3'-benzophenonetetracarboxylic acid, 2,2-bis(3,4-dicarboxyphenyl)hexafluoropropane, 2,2-bis(2,3-dicarboxyphenyl)hexafluoropropane, 1,1-bis(3,4-dicarboxyphenyl)ethane, 1,1-bis(2,3-dicarboxyphenyl)ethane, bis(3,4-dicarboxyphenyl)methane, bis(2,3-dicarboxyphenyl) Aromatic tetracarboxylic acids such as (3,4-dicarboxyphenyl) sulfone, (3,4-dicarboxyphenyl) ether, 1,2,5,6-naphthalenetetracarboxylic acid, 2,3,6,7-naphthalenetetracarboxylic acid, 2,3,5,6-pyridinetetracarboxylic acid, 3,4,9,10-perylenetetracarboxylic acid, or cyclobutanetetracarboxylic acid, 1,2,3,4-cyclopentanetetracarboxylic acid, cyclohexanetetracarboxylic acid, bicyclo[2.2.1.]heptanetetracarboxylic acid, bicyclo[3.3.1.]tetracarboxylic acid, bicyclo[3.1.1.]hept-2-enetetracarboxylic acid, bicyclo[2.2.2.]octanetetracarboxylic acid, adamantanetetracarboxylic acid, etc., but not limited to these. These acids can be used alone or in combination of two or more.
[0056] The structure represented by general formula (2) is a structural unit of polyamide-imide. The structure represented by general formula (3) is a structural unit of polyamide. The structure represented by general formula (4) is a structural unit of polyurea. The structure represented by general formula (5) is a structural unit of polyazole.
[0057] In general formulas (2) and (4), R 3 R 7 This represents a diamine residue. Examples of amine components that provide diamine residues include R, which corresponds to the general formula (1). 1 The amine component in the description is the same as the amine component.
[0058] In general formula (2), R 4 This refers to a tricarboxylic acid residue. Examples of acid components that provide tricarboxylic acid residues include trimellitic acid, pyromellitic acid, diphenyl ether tricarboxylic acid, and biphenyl tricarboxylic acid, but are not limited to these. These acids can be used alone or in combination of two or more.
[0059] In general formula (4), R 8 The term represents a diisocyanate residue, which is a divalent group having 2 to 50 carbon atoms. As a diisocyanate component providing the diisocyanate residue, R of the general formula (1) can be listed as an example. 1 The structure described above is formed by substituting the amino group of the diamine with an isocyanate group. These diisocyanate groups can be used alone or in combination of two or more.
[0060] In general formula (5), R 10 This indicates a diamine residue formed by the ortho-position bonding of the group represented by XH with respect to an amino group. X represents a unit selected from -O-, -S-, -NH-, and -C(=O)O-. Polyazoles can be obtained by dehydration and ring closure through ortho-position placement. As a source of -R... 20 The diamine components represented by the (XH)2- structure of diamine residues can be listed as follows: bis(3-amino-4-hydroxyphenyl)hexafluoropropane, bis(3-amino-4-hydroxyphenyl)sulfone, bis(3-amino-4-hydroxyphenyl)propane, bis(3-amino-4-hydroxyphenyl)methylene, bis(3-amino-4-hydroxyphenyl) ether, bis(3-amino-4-hydroxy)biphenyl, bis(3-amino-4-hydroxyphenyl)fluorene, bis(4-amino-... Diamines containing hydroxyl groups, such as bis(4-amino-3-hydroxyphenyl)hexafluoropropane, bis(4-amino-3-hydroxyphenyl)sulfone, bis(4-amino-3-hydroxyphenyl)propane, bis(4-amino-3-hydroxyphenyl)methylene, bis(4-amino-3-hydroxyphenyl) ether, bis(4-amino-3-hydroxy)biphenyl, bis(4-amino-3-hydroxyphenyl)fluorene, etc., or amines formed by substituting the hydroxyl groups of these diamines with thiol, amino, or carboxyl groups, are not limited to these. These amines can be used alone or in combination of two or more.
[0061] In general formula (3), R 5 This represents a diamine residue. Examples of amine components that provide diamine residues include R, which corresponds to the general formula (1). 1 The description of the amine component is the same as that of the amine component, but does not include amine components such as R. 10 The XH group represents a diamine residue formed by bonding the amino group to the amino group at the ortho position.
[0062] In general formulas (3) and (5), R 6 R 9 This refers to a dicarboxylic acid residue. Examples of acid components providing dicarboxylic acid residues include: terephthalic acid, isophthalic acid, diphenyl ether dicarboxylic acid, diphenyl sulfone dicarboxylic acid, diphenyl sulfide dicarboxylic acid, biphenyl dicarboxylic acid, 2,2'-bis(4-carboxyl)hexafluoropropane, 2,2'-bis(4-carboxyl)propane, diphenyl ketone dicarboxylic acid, etc., but are not limited to these. These acids can be used alone or in combination of two or more.
[0063] From the viewpoint that the resin composition exhibits minimal deterioration when stored at room temperature and has little impact on spinning properties even after prolonged storage at room temperature, a heat-resistant resin containing nitrogen atoms is most preferably a resin having a polyamide-imide structure represented by general formula (2). By having both an amide structure and an imide structure, it exhibits good compatibility with (b) the solvent and (c) the fluoroalkyl surfactant, and has the advantage of suppressing bead formation even after long-term storage at room temperature.
[0064] The preferred form is R in general formula (2). 3 It has residues of 3,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylmethane, 3,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone, 3,4'-diaminodiphenyl sulfide, 4,4'-diaminodiphenyl sulfide, or the structure represented by the following general formula (6) or general formula (7).
[0065] Regarding the aspect of obtaining fine-diameter fibers during spinning, concerning R in general formula (1) 1 R in general formula (2) 3 R in general formula (3) 5 R in general formula (3) 6 R in general formula (4) 7 R in general formula (4) 8 and R in general formula (5) 9 Preferably, 30 mol% or more, more preferably 50 mol% or more of these have the structure represented by the general formula (6) or general formula (7), typically the structure represented by general formula (6) or general formula (7).
[0066] [Chemistry 6]
[0067]
[0068] In general formula (6), R 11 The monovalent group representing carbons 1 to 6 is located adjacent to the polymer backbone. n1 represents an integer from 1 to 4, preferably 1 or 2.
[0069] [Chemistry 7]
[0070]
[0071] In general formula (7), R 12 and R 13 Each of the following groups independently represents a monovalent group having 1 to 6 carbon atoms, located in an adjacent position relative to the polymer backbone. n2 and n3 independently represent integers from 1 to 4, preferably 1 or 2. Additionally, X2 represents at least one selected from single bonds, -O-, -S-, -CH2-, -C(CH3)2-, and -C(CF3)2-.
[0072] As R 11 ~R 13 Preferred examples include methyl, ethyl, propyl, butyl, hexyl, and cyclohexyl, but are not limited to these. Methyl and ethyl are more preferred.
[0073] As a further preferred example of the structure represented by general formula (6) or general formula (7), the following structures can be listed.
[0074] [Chemistry 8]
[0075]
[0076] [Chemistry 9]
[0077]
[0078] Resins having the structures represented by these general formulas (1) to (5) do not require high-temperature heating for dehydration and ring closure. Therefore, shrinkage of the filaments caused by dehydration and ring closure can be suppressed, thereby obtaining nonwoven fabrics with higher shape stability.
[0079] Resins having structures represented by general formulas (1) to (5) can be obtained by reacting a diamine or a diisocyanate providing the same diamine residue, or a trimethylsilylated diamine providing the same diamine residue, with a tetracarboxylic acid derivative, a tricarboxylic acid derivative, a dicarboxylic acid derivative, or a diisocyanate in a known bipolar solvent such as N-methylpyrrolidone or dimethylacetamide. In the case of resins having structures represented by general formulas (3) or (4), a reaction temperature of -5°C to 80°C is suitable. Furthermore, in the case of resins having structures represented by general formulas (1), (2), or (5), a temperature of -5°C to 250°C is suitable.
[0080] There are no particular restrictions on the organic solvent used as the reaction medium, as long as it can dissolve the resin. Generally speaking, aprotic polar solvents are preferred. Examples include: diphenyl sulfone, dimethyl sulfoxide, sulfolane, dimethyl sulfone, N,N-dimethylformamide, N,N-dimethylacetamide, N,N-dimethylisobutylamide, 3-methoxy-N,N-dimethylpropaneamide, 3-butoxy-N,N-dimethylpropaneamide, N-methyl-2-pyrrolidone, diethyl sulfone, diethyl sulfoxide, 1,4-dimethylbenzimidazolidinone, hexamethyltriamide, 1,3-dimethylimidazolium ketone, etc. In addition, high-boiling-point ketone solvents such as cyclohexanone, ether solvents such as ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, diethylene glycol methyl ethyl ether, diethylene glycol diethyl ether, propylene glycol dimethyl ether, propylene glycol diethyl ether, dipropylene glycol dimethyl ether, dipropylene glycol dimethyl ether, dipropylene glycol diethyl ether, dipropylene glycol dimethyl ether, dipropylene glycol diethyl ether, dipropylene glycol diethyl ether, and dipropylene glycol diethyl ether, as well as aromatic hydrocarbon solvents such as toluene and xylene, and ester solvents such as propylene glycol monomethyl ether acetate and methyl-methoxybutanol acetate, can also be added.
[0081] The amount of solvent used in polycondensation is preferably 50 parts by weight or more, more preferably 100 parts by weight or more, relative to 100 parts by weight of all monomers. By setting the amount of solvent to 50 parts by weight or more relative to the total monomers, operations such as stirring become easier, and the polycondensation reaction proceeds smoothly. On the other hand, it is preferably 500 parts by weight or less, more preferably 250 parts by weight or less. By setting it to 500 parts by weight or less, the monomer concentration in the solvent becomes higher, the polymerization rate increases, and therefore high molecular weight polymers with a weight average molecular weight of 10,000 or more can be easily obtained.
[0082] The weight-average molecular weight of the resin in this invention is preferably in the range of 5,000 to 300,000, and particularly preferably in the range of 10,000 to 200,000. Furthermore, the weight-average molecular weight in this invention refers to a value determined using gel permeation chromatography (GPC) with a solvent containing 1M lithium chloride in a mixed solvent of N-methyl pyrrolidone (NMP) / H3PO4, and calculated using a calibration curve of standard polystyrene.
[0083] (a-2) Precursors of heat-resistant resins containing nitrogen atoms
[0084] Preferred precursors for heat-resistant resins containing nitrogen atoms include, for example, polyimide precursors, polyamide-imide precursors, and polyazole precursors. When using these precursors, heat treatment at 120°C to 500°C is required for dehydration and ring closure after spinning.
[0085] Specifically, it refers to resins having the structures represented by the following general formulas (8) to (10).
[0086] [Chemistry 10]
[0087]
[0088] In general formula (8), R 14 R represents a divalent group with 2 to 50 carbon atoms. 15 Represents a tetravalent group with 4 to 50 carbon atoms. R 16 Indicates selection from OH, OR 17 and O - R 18+ At least one of them. R 17 Represents a monovalent base with 1 to 10 carbon atoms. R 18+ This indicates a monovalent metal cation or ammonium ion. m6 represents an integer from 1 to 10000.
[0089] [Chemistry 11]
[0090]
[0091] In general formula (9), R 19 R represents a divalent group with 2 to 50 carbon atoms. 20 R represents a trivalent group with 4 to 50 carbon atoms. 21 Indicates selection from OH, OR 22 and O - R 23+ At least one of them. R 22 Represents a monovalent base with 1 to 10 carbon atoms. R 23+ This indicates a monovalent metal cation or ammonium ion. m7 represents an integer from 1 to 10000.
[0092] [Chemistry 12]
[0093]
[0094] In general formula (10), R 24 R represents a divalent group with 2 to 50 carbon atoms. 25 This indicates a trivalent group with 4 to 50 carbon atoms. m8 represents an integer from 1 to 10000.
[0095] Furthermore, R 14 R 15 R 17 R 19 R 20 R 22 R 24 and R 25 Typically, these are residues of aliphatic hydrocarbons, aromatic hydrocarbons, and nitrogen-containing aromatic hydrocarbons. In addition, they also include those formed by linkages such as single bonds, ether bonds, thioether bonds, ester bonds, ketone bonds, and sulfone bonds, or those formed by substitution of a portion of hydrogen with monovalent functional groups such as alkyl, haloalkyl, oxyalkyl, oxyaryl, nitro, cyano, and halogen.
[0096] The structure represented by general formula (8) is a structural unit of polyimide precursor. The structure represented by general formula (9) is a structural unit of polyamide-imide precursor. The structure represented by general formula (10) is a structural unit of polyazole precursor.
[0097] In general formulas (8) and (9), R 14 R 19 This represents a diamine residue. Examples of amine components that provide diamine residues include R, which corresponds to the general formula (1). 1 The amine component in the description is the same as the amine component.
[0098] In general formula (10), R 24 This represents a diamine residue. Examples of amine components providing diamine residues include R, which corresponds to the general formula (5).10 The amine component in the description is the same as the amine component.
[0099] In general formula (8), R 15 This represents a tetracarboxylic acid residue. Examples of acid components providing tetracarboxylic acid residues include R, which corresponds to the general formula (1). 2 The acid component in the description is the same as the acid component.
[0100] In general formula (9), R 20 This represents a tricarboxylic acid residue. Examples of acid components providing tricarboxylic acid residues include R, which corresponds to the general formula (2). 4 The acid component in the description is the same as the acid component.
[0101] In general formula (10), R 25 This represents a dicarboxylic acid residue. As acidic components providing dicarboxylic acid residues, examples include R of the general formula (5). 9 The acid component in the description is the same as the acid component.
[0102] In general formulas (8) and (9), from the viewpoint of suppressing the breakage of filaments caused by shrinkage during dehydration and closure, R 17 R 22 Preferred groups include methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl, hexyl, cyclohexyl, etc., but are not limited to these. These groups can be used alone or in combination of two or more.
[0103] In general formulas (8) and (9), R is used as... 18+ R 23+ Specific examples include sodium ions, potassium ions, and lithium ions, but are not limited to these. Specific examples of ammonium ions include: ammonium ions formed by the addition of hydrogen to trialkylamines such as trimethylamine, triethylamine, and triisopropanolamine; ammonium ions formed by the addition of hydrogen to monoamines containing heterocycles such as pyridine, imidazole, and piperidine; and quaternary ammonium ions such as tetramethylammonium and tetrabutylammonium, but are not limited to these. These metal cations and ammonium ions can be used alone or in combination of two or more.
[0104] Regarding the aspect of obtaining fine-diameter fibers during spinning, concerning R in general formula (8) 14 R in general formula (9) 19 R in general formula (10) 24 Preferably, 30 mol% or more, more preferably 50 mol% or more of these have the structure represented by the general formula (6) or general formula (7), typically the structure represented by general formula (6) or general formula (7).
[0105] (a-3) Heat-resistant resins having groups selected from the group consisting of ether, ketone, sulfone, and thioether groups in their main chain.
[0106] The term "heat-resistant resin" refers to a resin whose main chain contains groups selected from ketone, sulfone, and thioether groups. For example, it refers to a resin in which aromatic rings or heterocycles such as phenyl or naphthyl are linked by these linking groups to form a polymeric main chain, and the resin has a temperature of 200°C or higher when the weight of the resin decreases by 5%.
[0107] As a heat-resistant resin having at least one linker selected from ketone, sulfone, and thioether groups in the main chain, the following are preferred examples: polyetherketone, polyetheretherketone, polyethersulfone, polyphenylene sulfide, etc.
[0108] (a-4) A precursor of a heat-resistant resin having groups selected from the group consisting of ether, ketone, sulfone, and thioether groups in its main chain.
[0109] Preferred precursors for heat-resistant resins having groups selected from the group consisting of ether, ketone, sulfone, and thioether groups in the main chain include, for example, polyetherketone precursors, polyetheretherketone precursors, polyethersulfone precursors, and polyphenylene sulfide precursors. When using these precursors, heat treatment at 120°C to 500°C can be performed to convert them into the corresponding heat-resistant resin in order to perform dehydration and ring-closure after spinning.
[0110] (b) Solvent
[0111] As for the solvent (b) used in the resin composition of the present invention, there are no particular limitations as long as it is a solvent capable of dissolving the resin of component (a). A solvent used as a reaction solvent during resin manufacturing may also be used directly.
[0112] In addition, at this time, besides the aforementioned reaction solvent, undesirable solvents may be included within a range that does not precipitate resin. Examples of solvents used at this time include: ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, ethylene glycol dibutyl ether, diethylene glycol diethyl ether, diethylene glycol dimethyl ether, diethylene glycol methyl ethyl ether, etc. (ether-based solvents), ethylene glycol monoethyl ether acetate, propylene glycol monomethyl ether acetate, propyl acetate, butyl acetate, isobutyl acetate, 3-methoxybutyl acetate, 3- Ester solvents such as methyl-3-methoxybutylacetate, methyl lactate, ethyl lactate, and butyl lactate; ketones such as acetylacetone, methyl propyl ketone, methyl butyl ketone, methyl isobutyl ketone, cyclopentanone, and 2-heptanone; alcohols such as butanol, isobutanol, pentanol, 4-methyl-2-pentanol, 3-methyl-2-butanol, 3-methyl-3-methoxybutanol, and diacetone alcohol; aromatic hydrocarbons such as toluene and xylene; and water, but not limited to these. These can be used alone or in combination.
[0113] (c) Surfactants containing fluoroalkyl groups
[0114] The resin composition of the present invention, by comprising (c) a surfactant having a fluoroalkyl group, reduces the surface tension of the resin composition and stabilizes spinning. Therefore, the formation of nodular defects, i.e., "beads," caused by a sudden increase in fiber diameter, can be suppressed.
[0115] The fluoroalkyl group is a group containing a perfluorinated group. From the viewpoint of increasing the effect of reducing surface tension, the number of carbon atoms in the perfluorinated group is preferably 3 or more, more preferably 4 or more. In addition, from the viewpoint of generating appropriate charge repulsion during electrospinning so as to adjust the fiber system to a more preferred range, the number is preferably 12 or less, more preferably 8 or less.
[0116] The number of fluoroalkyl groups contained in one molecule of the surfactant compound is preferably 1 to 3, more preferably 1 to 2.
[0117] From the viewpoint of further suppressing bead formation, (c) a surfactant having a fluoroalkyl group is preferably a surfactant having at least one group selected from oxyvinyl, oxypropylene, and groups containing quaternary nitrogen. These groups are believed to contribute to stabilization during the spinning process through interaction with the carbonyl or nitrogen groups of the resin.
[0118] Specific examples of preferred groups as oxyethylene and oxypropylene groups are those in the structures represented by the following general formulas (11) and (12), where n4 and n5 are 2 to 20, and more preferably 2 to 11.
[0119] [Chemistry 13]
[0120] -(CH2CH2O)n4- (11)
[0121] [Chemistry 14]
[0122]
[0123] Examples of groups containing quaternary nitrogen include quaternary ammonium structures and amine oxide structures. From the viewpoint of reducing the number of beads, amine oxide structures are more preferred.
[0124] Furthermore, regarding electric field spinning, from the viewpoint of promoting liquid splitting caused by charge repulsion during the spinning process and contributing to fiber diameter reduction, (c) the surfactant with fluoroalkyl groups is preferably a surfactant having at least one structure selected from carboxyl, sulfone, hydroxyl, carboxylate, sulfonate, and phenolic hydroxyl salts. More preferably, (c) the surfactant with fluoroalkyl groups has at least one structure selected from carboxyl and hydroxyl groups.
[0125] Surfactants containing a fluoroalkyl group having at least one group selected from oxyvinyl, oxypropylene and a group containing a quaternary nitrogen are preferably used together with surfactants containing a fluoroalkyl group having at least one structure selected from carboxyl, sulfone, hydroxy, carboxylate, sulfonate and phenolic hydroxyl salt.
[0126] Furthermore, from the viewpoint of further reducing the number of beads, (c) the surfactant having a fluoroalkyl group is preferably not having a structure consisting of repeating units containing a fluoroalkyl group linked together.
[0127] Here, the structure formed by linking repeating units containing fluoroalkyl groups refers to a structure obtained by linking five or more fluoroalkyl compounds as monomers through polymerization reactions such as addition polymerization or condensation polymerization. Examples of such substances include oligomers or polymers formed by repeating five or more repeating units containing fluoroalkyl groups in the side chains, as shown in the following formula.
[0128] [Chemistry 15]
[0129]
[0130] On the other hand, a molecule containing multiple fluoroalkyl groups that are not repeating units, such as those shown in the following formula, or a molecule containing repeating structures but without fluoroalkyl groups, is not equivalent to a structure formed by repeating units containing fluoroalkyl groups linked together.
[0131] [Chemistry 16]
[0132]
[0133] [Chemistry 17]
[0134] C8F 17 CH2CH2-(CH2CH2O) 10 -CH2CH2OH
[0135] As preferred examples of surfactants having fluoroalkyl groups (c), the following compounds can be listed.
[0136] [Chemistry 18]
[0137]
[0138] In general formula (13), R 26 This represents a monovalent base with 1 to 6 carbon atoms. n6 represents an integer from 1 to 15, n7 represents an integer from 1 to 4, and n8 represents an integer from 2 to 10000.
[0139] [Chemistry 19]
[0140] F(CF2)n9(CH2)n 10-Y1 (14)
[0141] In general formula (14), n9 represents an integer from 1 to 15, n 10 Represents an integer from 1 to 4. Y1 represents a group selected from carboxyl, sulfonic acid, hydroxyl, carboxylate, sulfonate, and phenolic hydroxyl salt structures.
[0142] [Chemistry 20]
[0143] F(CF2)n 11 (CH2)n 12 -(CH2CH2O)n 13 -CH2CH2-Y2 (15)
[0144] In general formula (15), n 11 n represents an integer from 1 to 15. 12 n represents an integer from 1 to 4. 13 Y2 represents an integer from 1 to 20. Y2 represents a group selected from carboxyl, sulfonic acid, and hydroxyl groups, and includes metal salts such as alkali metal salts and alkaline earth metal salts of these groups.
[0145] [Chemistry 21]
[0146] F(CF2)n 14 (CH2)n 15 -(CH2CH2O)n 16 -CH2CH2-(CH2)n 17 (CF2)n 18 F (16)
[0147] In general formula (16), n 14 and n 18 Each of the integers from 1 to 15 can be represented independently, and n 15 and n 17 Each of the integers from 1 to 4 can be represented independently, and n 16 Represents integers from 1 to 20.
[0148] [Chemistry 22]
[0149]
[0150] In general formula (17), n 19 and n 21 Each of the integers from 1 to 15 can be represented independently, and n 20 and n 22 Each of the integers from 1 to 4 can be represented independently, n 23 Y3 represents an integer from 1 to 20. Y3 is a direct bond, an ether group, or a thioether group. Y4 represents a group selected from carboxyl, sulfonic acid, and hydroxyl groups, and includes metal salts such as alkali metal salts and alkaline earth metal salts of these groups.
[0151] [Chemistry 23]
[0152] F(CF2)n 24 (CH2)n 25 -Y5-(CH2)n 26 -Y6 (18)
[0153] In general formula (18), n 24 n represents an integer from 1 to 15. 25 n represents an integer from 1 to 4. 26 Represents integers from 1 to 8. Y5 is a direct bond, ether group, or thioether group. Y6 represents a group selected from carboxyl, sulfonic acid, and hydroxyl groups, and includes metal salts such as alkali metal salts and alkaline earth metal salts of these groups.
[0154] [Chemistry 24]
[0155]
[0156] In general formula (19), R 27 and R 28 Each of the following groups independently represents a divalent group having 1 to 6 carbon atoms. R 29 and R 30 Each group independently represents a monovalent group having 1 to 6 carbon atoms. Y7 represents a group selected from direct bonds, ether groups, thioether groups, -NH-, and -NR. 31 - the base in R. 31 A monovalent base representing carbon numbers from 1 to 6. 27 Represents integers from 1 to 15.
[0157] In general formulas (13) to (19), from the viewpoint of increasing the effect of reducing surface tension, n6, n9, n 11 n 14 n 18 n 19 n 21 n 24 and n 27 Preferably, the diameter is 3 or more, more preferably 4 or more. Furthermore, from the viewpoint of reducing fiber diameter, it is preferably 12 or less, more preferably 8 or less.
[0158] In general formulas (13) to (18), from the viewpoint of reducing surface tension, n7, n 10 n 12 n 15 n 17 n 20 n 22 and n 25 The preferred value is 2.
[0159] In general formula (18), from the viewpoint of reducing surface tension, n 26 The preferred values are 2 to 4.
[0160] In general formulas (15) to (17), from the viewpoint of reducing the number of beads, n 13 n 16 and n 23 Preferably 2 to 15, and more preferably 2 to 11.
[0161] In general formulas (14), (15), (17), and (18), from the viewpoint of fiber diameter reduction, Y1, Y2, Y4, and Y6 are preferably groups selected from carboxyl and hydroxyl groups.
[0162] In general formula (19), from the viewpoint of reducing surface tension, R 27 and R 28 Preferably, it has a carbon number of 1 to 4. Furthermore, from the viewpoint of fiber fineness, R 27 More preferably, the side chain contains a group with 1 to 4 carbon atoms, including a hydroxyl or carboxyl group.
[0163] In general formula (19), from the viewpoint of reducing surface tension, R 29 R 30 and R 31 Preferably, the group has 1 to 3 carbon atoms. Preferred specific examples are methyl, ethyl, and isopropyl.
[0164] Furthermore, R 26 ~R 31 Typically, these are residues of aliphatic hydrocarbons, aromatic hydrocarbons, and nitrogen-containing aromatic hydrocarbons. In addition, they also include those formed by linkages such as single bonds, ether bonds, thioether bonds, ester bonds, ketone bonds, and sulfone bonds, or those formed by the substitution of a portion of hydrogen with monovalent functional groups such as alkyl, oxyalkyl, oxyaryl, nitro, and cyano.
[0165] (c) Particularly preferred examples of surfactants having fluoroalkyl groups are the compounds represented below.
[0166] [Chemistry 25]
[0167] C4F9CH2CH2-(CH2CH2O)8-CH2CH2OH
[0168] C6F 13 CH2CH2-(CH2CH2O)8-CH2CH2OH
[0169] C6F 13 CH2CH2-(CH2CH2O) 10 -CH2CH2OH
[0170] C8F17 CH2CH2-(CH2CH2O)2-CH2CH2OH
[0171] C8F 17 CH2CH2-(CH2CH2O)4-CH2CH2OH
[0172] C8F 17 CH2CH2-(CH2CH2O)6-CH2CH2OH
[0173] C8F 17 CH2CH2-(CH2CH2O)8-CH2CH2OH
[0174] C8F 17 CH2CH2-(CH2CH2O) 10 -CH2CH2OH
[0175] C6F 13 CH2CH2-(CH2CH2O)8-CH2CH2COOH
[0176] C8F 17 CH2CH2-(CH2CH2O)8-CH2CH2COOH
[0177] [Chemical Formula 26]
[0178] C4F9CH2CH2-(CH2CH2O)4-CH2CH2-CH2CH2C4F9
[0179] C4F9CH2CH2-(CH2CH2O)8-CH2CH2-CH2CH2C4F9
[0180] C4F9CH2CH2-(CH2CH2O) 10 -CH2CH2-CH2CH2C4F9
[0181] C6F 13 CH2CH2-(CH2CH2O)8-CH2CH2-CH2CH2C6F 13
[0182] C8F 17 CH2CH2-(CH2CH2O) 10 -CH2CH2-CH2CH2C8F 17
[0183] [Chemical Formula 27]
[0184]
[0185] [Chemical Formula 28]
[0186]
[0187] C8F 17 CH2CH2-S-C4H8-SO3Li
[0188] C8F 17 CH2CH2-S-C2H4-SO3Li
[0189] C8F 17 CH2CH2-O-C4H8-SO3H
[0190] C6F 13 CH2CH2-S-C4H9-SO3Li
[0191] [Chemistry 29]
[0192]
[0193] In the composition of the present invention used to form nonwoven fabric by electric field spinning, the content of the fluoroalkyl surfactant (c) in the composition is preferably 0.3% to 10% by mass, more preferably 0.5% to 5% by mass, and even more preferably 1% to 3% by mass. By having its content at or above the lower limit, the frequency of nodular defects in the fibers during electric field spinning can be further suppressed. Furthermore, by having its content at or below the upper limit, the charge repulsion during electric field spinning is within an appropriate range, making it easier to obtain filaments with small fiber diameters.
[0194] <Non-woven fabric>
[0195] The nonwoven fabric of the present invention comprises: (a) at least one heat-resistant resin or a precursor thereof selected from the group consisting of heat-resistant resins containing nitrogen atoms and heat-resistant resins having at least one group selected from ether, ketone, sulfone and thioether groups in the main chain; and (c) a surfactant having a fluoroalkyl group. Details of components (a) and (c) are as described herein.
[0196] Furthermore, in the case of nonwoven fabrics using heat-resistant resin precursors, they can be converted into heat-resistant resins through heat treatment or chemical treatment such as cross-linking, thermal ring-closing, or chemical ring-closing.
[0197] By including component (c) in the nonwoven fabric, the bonding at the points where the fibers contact each other is enhanced due to the hydrophobic interaction caused by the fluoroalkyl groups that are predominantly present on the fiber surface, thus increasing the strength and toughness of the nonwoven fabric. Furthermore, when heat treatment is applied after the nonwoven fabric is formed, it has the advantage that the bonding between the polymer fibers becomes stronger due to the fusion of the fluoroalkyl groups.
[0198] Such nonwoven fabrics can be obtained, for example, by melting or dissolving a resin composition in a solvent and spinning the result, wherein the resin composition comprises: (a) at least one heat-resistant resin or a precursor thereof selected from the group consisting of heat-resistant resins containing nitrogen atoms and heat-resistant resins having at least one group selected from ether, ketone, sulfone and thioether groups in the main chain; (b) a solvent; and (c) a surfactant having a fluoroalkyl group.
[0199] As a method for spinning, electric field spinning is preferred because the liquid splits during spinning, thereby obtaining a nonwoven fabric containing fibers with finer diameters. Specifically, it is preferable to form a nonwoven fabric by spinning the resin composition using an electric field spinning method.
[0200] The electric field spinning method used here refers to the following spinning method: by applying a high voltage to a polymer solution and blowing the charged polymer solution onto a grounded counter electrode, extremely fine fibers are obtained. There are no particular limitations on the electric field spinning apparatus used in this invention; examples include apparatuses that eject polymer solutions from protruding nozzles, such as syringe syringes, or apparatuses that eject extremely fine fibers from an ejection section by charging a thin film of polymer solution formed on a rotating roller or ball. If a voltage is applied to the ejection section while the liquid is ejected, and an aluminum foil or release paper as a substrate is pre-attached to the grounded counter electrode, the nonwoven fabric accumulates on the substrate.
[0201] Furthermore, nonwoven fabrics formed from resin compositions comprising the general formulas (1) to (5) do not require heat treatment for dehydration and loop closure after spinning, thereby making it extremely easy to obtain nonwoven fabrics with excellent heat resistance and mechanical properties.
[0202] On the other hand, regarding the formation of nonwoven fabrics using heat-resistant resin precursors, heat-resistant resin precursors generally have a high affinity for the solvent, thus exhibiting excellent filamentability. This property allows for the acquisition of nonwoven fabrics with fine fibers. Furthermore, by converting the heat-resistant resin precursor into a heat-resistant resin, nonwoven fabrics with excellent heat resistance and mechanical properties can be obtained.
[0203] Nonwoven fabrics with excellent mechanical strength are resistant to breakage and will not break even when the volume of the electrodes changes during battery assembly or charging and discharging. In this regard, the tensile strength of the nonwoven fabric is preferably 1.0 N / cm or higher, more preferably 1.5 N / cm or higher, even more preferably 2.0 N / cm or higher, and particularly preferably 2.5 N / cm or higher. There is no particular limit to the upper limit of the tensile strength, but it is preferably 5.0 N / cm or lower.
[0204] The fiber diameter in the nonwoven fabric is preferably 3 μm or less, more preferably 1.5 μm or less, and even more preferably 1 μm or less. The smaller the fiber diameter, the higher the porosity can be while maintaining the nonwoven fabric in a dense and strong state, and the higher the air permeability and liquid permeability can be ensured.
[0205] The fiber diameter mentioned here is obtained by observing the nonwoven fabric at an appropriate magnification (e.g., 10,000x) using a scanning electron microscope (SEM), randomly selecting 30 fibers within the field of view, measuring their width, and taking their arithmetic mean.
[0206] <Uses of Non-woven Fabric>
[0207] The nonwoven fabric of the present invention can preferably be used in fiber products such as separators for energy storage components such as secondary batteries or double-layer capacitors, sound-absorbing materials, electromagnetic wave shielding materials, separation filters, or heat-resistant bag filters. In particular, when used as a separator for energy storage components, it can improve the safety of energy storage components by being a separator with high heat resistance.
[0208] The secondary battery or electric double-layer capacitor of the present invention has the separator as a separator between the positive and negative electrodes. This type of secondary battery or electric double-layer capacitor can be obtained by stacking multiple electrodes with the separator in between and sealing them together with the electrolyte in an outer packaging material such as a metal casing.
[0209] Example
[0210] The following examples and techniques are provided to illustrate the present invention, but the present invention is not limited to these examples.
[0211] Synthesis Example 1 (polyethersulfone solution)
[0212] Under a dry nitrogen stream, 22.8 g (0.1 mol) of bisphenol A (Tokyo Chemical Co., Ltd.), 28.7 g (0.1 mol) of bis(4-chlorophenyl) sulfone (Tokyo Chemical Co., Ltd.), 17.3 g (0.125 mol) of potassium carbonate (Tokyo Chemical Co., Ltd.), 150 g of N,N-dimethylacetamide (Tokyo Chemical Co., Ltd., DMAc), and 80 g of toluene (Tokyo Chemical Co., Ltd.) were placed in a 500 mL flask containing a Dean-Stark collector. The mixture was circulated with stirring for 6 hours, and water was removed. Then, excess toluene was removed under reduced pressure, and the remaining mixture was stirred at 160 °C for 12 hours. The reaction solution was cooled to 100 °C, 100 g of chlorobenzene (Tokyo Chemical Co., Ltd.) was added, and the precipitate was separated by filtration. After neutralizing the filtrate with acetic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), the filtrate was added to 3L of a liquid solution with a 1:1 mass ratio of pure water and methanol (manufactured by Tokyo Chemical Industry Co., Ltd.) to precipitate the polymer, which was then separated by filtration. The precipitate was further dispersed and filtered using 3L of a 1:1 mass ratio of pure water and methanol, followed by dispersion and filtration using 3L of pure water. Finally, the solution was circulated in boiling water for 1 hour. The powder separated by filtration after circulation was dried under reduced pressure at 100°C for 72 hours. 14g of the dried polymer solid was dissolved in 26g of DMAc to obtain a 35% (w / w) polyethersulfone solution (PES-01).
[0213] Synthesis Example 2 (Polyimide Precursor Solution)
[0214] Under a dry nitrogen stream, 10.8 g (0.1 mol) of p-phenylenediamine (Tokyo Chemical Co., Ltd., PDA) was dissolved in 50 g of DMAc in a 200 mL flask. 27.9 g (0.095 mol) of 3,3',4,4'-biphenyltetracarboxylic acid dianhydride (Tokyo Chemical Co., Ltd., BPDA) and 21.9 g of DMAc were added together. The mixture was stirred at 60 °C for 5 hours, then cooled to room temperature to obtain a polyimide precursor solution (PAA-01) with a polymer concentration of 35% by mass.
[0215] Synthesis Example 3 (Polyimide Solution)
[0216] Under a dry nitrogen stream, 33.0 g (0.09 mol) of 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane (manufactured by Tokyo Chemical Industry Co., Ltd., BAHF) was dissolved in 100 g of N-methyl-2-pyrrolidone (manufactured by Tokyo Chemical Industry Co., Ltd., NMP) in a 300 mL flask. 31.0 g (0.1 mol) of 3,3',4,4'-diphenyl ether tetracarboxylic acid dianhydride (manufactured by Tokyo Chemical Industry Co., Ltd., ODPA) and 12.8 g of NMP were added together, and the mixture was stirred at 40 °C for 2 hours. Then, the mixture was stirred at 200 °C for 6 hours, and cooled to room temperature to obtain a polyimide solution (PI-01) with a polymer concentration of 35% by mass.
[0217] Synthesis Example 4 (Polyamide-imide precursor solution)
[0218] Under a dry nitrogen stream, 20.0 g (0.1 mol) of diaminodiphenyl ether (DAE, manufactured by Tokyo Chemical Industry Co., Ltd.) and 11.1 g (0.11 mol) of triethylamine (TEA, manufactured by Tokyo Chemical Industry Co., Ltd.) were dissolved in 100 g of NMP in a 300 mL flask. 20.0 g (0.095 mol) of trimellitic anhydride chloride (TMC, manufactured by Tokyo Chemical Industry Co., Ltd.) and 20 g of NMP were added to the solution, and the mixture was stirred at 0 °C for 5 hours. After stirring, the precipitated triethylamine hydrochloride was separated by filtration, and the filtrate was added to 2 L of water. The polymer solid precipitate was collected by filtration. The precipitate was then washed three times with 2 L of water, and the collected polymer solid was dried in a vacuum dryer at 50 °C for 72 hours. 7 g of the dried polymer solid was dissolved in 13 g of DMAc to obtain a polyamide-imide precursor solution (PAIA-01) with a polymer concentration of 35% by mass.
[0219] Synthesis Example 5 (Polyamide-imide solution)
[0220] Under a dry nitrogen stream, 5.23 g (0.03 mol) of 2,4-toluene diisocyanate (Tokyo Chemicals, Inc., TDI) and 17.5 g (0.07 mol) of diphenylmethane diisocyanate (Tokyo Chemicals, Inc., MDI) were dissolved in 55 g of DMAc in a 300 mL flask. 18.3 g (0.095 mol) of trimellitic anhydride (Tokyo Chemicals, Inc., TMA) and 5.67 g of DMAc were then added to the solution. The mixture was stirred at 120°C for 2 hours, at 140°C for 2 hours, and at 160°C for 2 hours. After stirring, the mixture was cooled to room temperature to obtain a polyamide-imide solution (PAI-01) with a polymer concentration of 35% by mass.
[0221] Synthesis Example 6 (Polyamide Solution)
[0222] Under a dry nitrogen stream, 22.2 g (0.1 mol) of isophorone diisocyanate (Tokyo Chemical Co., Ltd., IHDI) was dissolved in 50 g of NMP in a 200 mL flask. 16.6 g (0.1 mol) of isophthalic acid (Tokyo Chemical Co., Ltd., IPA) and 5.71 g of NMP were added together, and the mixture was stirred at 200 °C for 6 hours. After stirring, the mixture was cooled to room temperature to obtain a polyamide solution (PA-01) with a polymer concentration of 35% by mass.
[0223] Synthesis Example 7 (Polyurea Solution)
[0224] Under a dry nitrogen stream, 10.8 g (0.1 mol) of PDA was dissolved in 50 g of DMAc in a 200 mL flask. 21.3 g (0.096 mol) of IHDI and 9.61 g of DMAc were then added together, and the mixture was stirred at 40 °C for 6 hours. After stirring, the mixture was cooled to room temperature to obtain a polyurea solution (PU-01) with a polymer concentration of 35% by mass.
[0225] Synthesis Example 8 (Polybenzoxazole precursor solution)
[0226] Under a dry nitrogen stream, 36.6 g (0.1 mol) of BAHF and 21.2 g (0.21 mol) of TEA were dissolved in 150 g of NMP in a 500 mL flask. 28.3 g (0.096 mol) of 4,4'-diphenyl ether dicarboxylic acid chloride (manufactured by Tokyo Chemical Industry Co., Ltd., DEDC) and 44.7 g of NMP were added to the solution, and the mixture was stirred at 5 °C for 6 hours. The precipitated triethylamine hydrochloride was separated by filtration, and the filtrate was added to 2 L of water. The polymer solid precipitate was collected by filtration. The precipitate was then washed three times with 2 L of water, and the collected polymer solid was dried in a vacuum dryer at 50 °C for 72 hours. 14 g of the dried polymer solid was dissolved in 26 g of DMAc to obtain a 35% (w / w) polybenzoxazole precursor solution (PBOA-01).
[0227] Synthesis Example 9 (Polybenzoxazole solution)
[0228] Under a dry nitrogen stream, 36.6 g (0.1 mol) of BAHF and 21.2 g (0.21 mol) of TEA were dissolved in 200 g of NMP in a 500 mL flask. 37.7 g (0.096 mol) of 2,2'-bis(4-carboxyphenyl)hexafluoropropane (manufactured by Tokyo Chemical Industry Co., Ltd., 6FDC) and 22.9 g of NMP were added to the solution, and the mixture was stirred at 40 °C for 2 hours. After stirring, the precipitated triethylamine hydrochloride was separated by filtration, and the filtrate was added to 2 L of water. The polymer solid precipitate was collected by filtration. The precipitate was then washed three times with 2 L of water, and the collected polymer solid was dried in a vacuum dryer at 50 °C for 72 hours. 28g of the dried polymer solid was dissolved in 52g of NMP, stirred at 200°C for 6 hours, and then cooled to room temperature to obtain a polybenzoxazole solution (PBO-01) with a polymer concentration of 35% by mass.
[0229] Synthesis Example 10 (Polybenzothiazole precursor solution)
[0230] Under a dry nitrogen stream, 24.5 g (0.1 mol) of 2,5-dimercapto-1,4-phenylene diamine dihydrochloride (manufactured by Tokyo Chemical Industry Co., Ltd., SHPDA) and 41.4 g (0.41 mol) of TEA were dissolved in 100 g of NMP in a 300 mL flask. 28.3 g (0.096 mol) of DEDC and 58.4 g of NMP were added to the solution, and the mixture was stirred at 5°C for 6 hours. The precipitated triethylamine hydrochloride was separated by filtration, and the filtrate was added to 2 L of water. The polymer solid precipitate was collected by filtration. The precipitate was then washed three times with 2 L of water, and the collected polymer solid was dried in a vacuum dryer at 50°C for 72 hours. 14 g of the dried polymer solid was dissolved in 26 g of DMAc to obtain a 35% by mass polybenzothiazole precursor solution (PBTA-01).
[0231] Synthesis Example 11 (Polybenzimidazole precursor solution)
[0232] Under a dry nitrogen stream, 21.4 g (0.1 mol) of 3,3'-diaminobenzidine (manufactured by Tokyo Chemical Industry Co., Ltd., DABZ) and 21.2 g (0.21 mol) of TEA were dissolved in 100 g of NMP in a 300 mL flask. 28.3 g (0.096 mol) of DEDC and 49.1 g of NMP were added to the solution, and the mixture was stirred at 5°C for 6 hours. The precipitated triethylamine hydrochloride was separated by filtration, and the filtrate was added to 2 L of water. The polymer solid precipitate was collected by filtration. The precipitate was then washed three times with 2 L of water, and the collected polymer solid was dried in a vacuum dryer at 50°C for 72 hours. 14 g of the dried polymer solid was dissolved in 26 g of DMAc to obtain a 35% by mass polybenzimidazole precursor solution (PBIA-01).
[0233] Synthesis Example 12 (Polyimide Precursor Solution)
[0234] Under a dry nitrogen stream, 14.0 g (0.07 mol) of DAE and 3.67 g (0.03 mol) of 2,4-diaminotoluene (Tokyo Chemical Co., Ltd., TDA) were dissolved in 70 g of DMAc in a 200 mL flask. 27.9 g (0.095 mol) of BPDA and 14.6 g of DMAc were then added to the solution. The mixture was stirred at 60 °C for 5 hours, then cooled to room temperature to obtain a polyimide precursor solution (PAA-02) with a polymer concentration of 35% by mass.
[0235] Synthesis Example 13 (Polyimide Precursor Solution)
[0236] Under a dry nitrogen stream, 10.0 g (0.05 mol) of DAE and 10.6 g (0.05 mol) of o-toluidine (manufactured by Tokyo Chemical Industry Co., Ltd., o-TODA) were dissolved in 70 g of DMAc in a 200 mL flask. Then, 20.7 g (0.095 mol) of pyromellitic anhydride (manufactured by Tokyo Chemical Industry Co., Ltd., PMDA) and 6.70 g of DMAc were added to the solution. The mixture was stirred at 60 °C for 5 hours, then cooled to room temperature to obtain a polyimide precursor solution (PAA-03) with a polymer concentration of 35% by mass.
[0237] Synthesis Example 14 (Polyimide Solution)
[0238] Under a dry nitrogen stream, 9.54 g (0.045 mol) of meta-toluidine (Tokyo Chemical Co., Ltd., m-TODA) and 11.2 g (0.045 mol) of 3,3-diaminodiphenyl sulfone (Tokyo Chemical Co., Ltd., 3-DDS) were dissolved in 80 g of NMP in a 300 mL flask. 31.0 g (0.1 mol) of ODPA and 10.1 g of NMP were then added to the solution, and the mixture was stirred at 40 °C for 2 hours. Subsequently, the mixture was stirred at 200 °C for 6 hours, and then cooled to room temperature to obtain a polyimide solution (PI-02) with a polymer concentration of 35% by mass.
[0239] Synthesis Example 15 (Polyimide Solution)
[0240] Under a dry nitrogen stream, 12.7 g (0.045 mol) of 4,4'-methylenebis(2-ethyl-6-methylaniline) (manufactured by Tokyo Chemical Industry Co., Ltd., MEDX) and 11.2 g (0.045 mol) of 3-DDS were dissolved in 80 g of NMP in a 300 mL flask. 10.9 g (0.05 mol) of PMDA, 16.1 g (0.05 mol) of 3,3',4,4'-benzophenone tetracarboxylic dianhydride (manufactured by Tokyo Chemical Industry Co., Ltd., BTDA) and 8.51 g of NMP were added to the solution, and the mixture was stirred at 40 °C for 2 hours. Then, the mixture was stirred at 200 °C for 6 hours, and cooled to room temperature to obtain a polyimide solution (PI-03) with a polymer concentration of 35% by mass.
[0241] Synthesis Example 16 (Polyimide Solution)
[0242] Under a dry nitrogen stream, 14.9 g (0.06 mol) of 3-DDS and 3.67 g (0.03 mol) of TDA were dissolved in 80 g of NMP in a 300 mL flask. 31.0 g (0.1 mol) of ODPA and 6.04 g of NMP were then added to the solution, and the mixture was stirred at 40 °C for 2 hours. Subsequently, the mixture was stirred at 200 °C for 6 hours, and then cooled to room temperature to obtain a polyimide solution (PI-04) with a polymer concentration of 35% by mass.
[0243] Synthesis Example 17 (Polyamide-imide precursor solution)
[0244] Under a dry nitrogen stream, 10.0 g (0.05 mol) of DAE, 10.6 g (0.05 mol) of m-TODA, and 11.1 g (0.11 mol) of triethylamine (Tokyo Chemical Co., Ltd., TEA) were dissolved in 100 g of NMP in a 300 mL flask. 20.0 g (0.095 mol) of TMC and 21.8 g of NMP were added to the solution, and the mixture was stirred at 0 °C for 5 hours. After stirring, the precipitated triethylamine hydrochloride was separated by filtration, and the filtrate was added to 2 L of water. The polymer solid precipitate was collected by filtration. The precipitate was then washed three times with 2 L of water, and the collected polymer solid was dried in a vacuum dryer at 50 °C for 72 hours. 7 g of the dried polymer solid was dissolved in 13 g of DMAc to obtain a 35% by mass polyamide-imide precursor solution (PAIA-02).
[0245] Synthesis Example 18 (Polyamide-imide solution)
[0246] Under a dry nitrogen stream, 13.2 g (0.05 mol) of o-toluidine diisocyanate (TODI, manufactured by Tokyo Chemical Industry Co., Ltd.) and 12.5 g (0.05 mol) of MDI were dissolved in 60 g of DMAc in a 300 mL flask. 18.3 g (0.095 mol) of TMA and 6.19 g of DMAc were then added to the solution. The mixture was stirred at 120°C for 2 hours, at 140°C for 2 hours, and at 160°C for 2 hours. After stirring, the mixture was cooled to room temperature to obtain a polyamide-imide solution (PAI-02) with a polymer concentration of 35% by mass.
[0247] Synthesis Example 19 (Polyamide-Imide Solution)
[0248] Under a dry nitrogen stream, 25.0 g (0.1 mol) of MDI was dissolved in 60 g of DMAc in a 300 mL flask. 18.3 g (0.095 mol) of TMA and 4.89 g of DMAc were then added together. The mixture was stirred at 120°C for 2 hours, at 140°C for 2 hours, and at 160°C for 2 hours. After stirring, the mixture was cooled to room temperature to obtain a polyamide-imide solution (PAI-03) with a polymer concentration of 35% by mass.
[0249] Synthesis Example 20 (Polyamide Solution)
[0250] Under a dry nitrogen stream, 15.5 g (0.07 mol) of IHDI and 5.23 g (0.03 mol) of TDI were dissolved in 45 g of NMP in a 200 mL flask. 16.6 g (0.1 mol) of IPA and 7.98 g of NMP were then added, and the mixture was stirred at 200 °C for 6 hours. After stirring, the mixture was cooled to room temperature to obtain a polyamide solution (PA-02) with a polymer concentration of 35% by mass.
[0251] Synthesis Example 21 (Polyamide Solution)
[0252] Under a dry nitrogen stream, 11.1 g (0.05 mol) of IHDI and 8.71 g (0.05 mol) of TDI were dissolved in 45 g of NMP in a 200 mL flask. 16.6 g (0.1 mol) of IPA and 6.28 g of NMP were then added, and the mixture was stirred at 200 °C for 6 hours. After stirring, the mixture was cooled to room temperature to obtain a polyamide solution (PA-03) with a polymer concentration of 35% by mass.
[0253] Synthesis Example 22 (Polyurea Solution)
[0254] Under a dry nitrogen stream, 14.0 g (0.07 mol) of DAE and 3.67 g (0.03 mol) of TDA were dissolved in 60 g of DMAc in a 200 mL flask. 21.3 g (0.096 mol) of IHDI and 12.4 g of DMAc were then added to the solution, and the mixture was stirred at 40 °C for 6 hours. After stirring, the solution was cooled to room temperature to obtain a polyurea solution (PU-02) with a polymer concentration of 35% by mass.
[0255] Synthesis Example 23 (Polyurea Solution)
[0256] Under a dry nitrogen stream, 5.4 g (0.05 mol) of PDA and 10.6 g (0.05 mol) of o-TODA were dissolved in 60 g of DMAc in a 200 mL flask. 21.3 g (0.096 mol) of IHDI and 9.27 g of DMAc were then added to the solution, and the mixture was stirred at 40 °C for 6 hours. After stirring, the solution was cooled to room temperature to obtain a polyurea solution (PU-03) with a polymer concentration of 35% by mass.
[0257] Synthesis Example 24 (Surfactant A: having a structure composed of repeating units containing fluoroalkyl groups)
[0258] 150 g of xylene was placed in a 500 mL flask equipped with a reflux condenser, thermometer, stirrer, and dropping funnel, and the liquid temperature was maintained at 110 °C. Under nitrogen, a mixed solution of 60 g (0.18 mol) of 2-(perfluorobutyl)ethyl methacrylate (manufactured by Fujifilm Wako Chemical Co., Ltd.), 2 g (0.02 mol) of methyl methacrylate (manufactured by Tokyo Chemical Industry Co., Ltd.), 38 g (0.2 mol) of n-butoxyethyl methacrylate (manufactured by Tokyo Chemical Industry Co., Ltd.), and 1 g of PEROCTA O (manufactured by Nippon Oil Co., Ltd.) was added dropwise to xylene over approximately 1 hour. The reaction was carried out at 110 °C for 2 hours to obtain compound A.
[0259] [Chemistry 30]
[0260]
[0261] Synthesis Example 25 (Surfactant B: Contains fluoroalkyl and oxyethylene groups)
[0262] In a 200 mL flask equipped with a stirrer and a dropping funnel, 19.3 g (0.1 mol) of 28% sodium methoxide methanol solution was added dropwise at room temperature to a mixture of 26.4 g (0.1 mol) of 1H,1H,2H,2H-nonafluoro-1-hexanol (manufactured by Tokyo Chemical Industry Co., Ltd.) and 16.0 g (0.05 mol) of bis(2-(2-(2-chloroethoxy)ethoxy)ethyl) ether (manufactured by Tokyo Chemical Industry Co., Ltd.). The mixture was then heated and stirred at 80 °C for 5 hours. After the reaction was complete, 300 mL of ethyl acetate was added, and the organic layer was washed three times with 150 mL of 20% saline solution. After drying with 30.0 g of anhydrous magnesium sulfate, the solvent was removed by vacuum distillation, thereby obtaining compound B.
[0263] [Chemistry 31]
[0264] C4F9CH2CH2-(CH2CH2O)4-CH2CH2-CH2CH2C4F9 B
[0265] Synthesis Example 26 (Surfactant C: containing fluoroalkyl, oxyethylene and hydroxyl groups)
[0266] In a 200 mL flask equipped with a stirrer and a dropping funnel, 19.3 g (0.1 mol) of 28% sodium methoxide methanol solution was added dropwise at room temperature to a mixture of 46.4 g (0.1 mol) of 1H,1H,2H,2H-heptadecylfluoro-1-decyl alcohol (manufactured by Tokyo Chemical Industry Co., Ltd.) and 16.9 g (0.1 mol) of 2-(2-(2-chloroethoxy)ethoxy)ethanol (manufactured by Tokyo Chemical Industry Co., Ltd.). The mixture was then heated and stirred at 80 °C for 5 hours. After the reaction was complete, 300 mL of ethyl acetate was added, and the organic layer was washed three times with 150 mL of 20% saline solution. After drying with 30.0 g of anhydrous magnesium sulfate, the solvent was removed by vacuum distillation, thereby obtaining compound C.
[0267] [Chemistry 32]
[0268] C8F 17 CH2CH2-(CH2CH2O)2-CH2CH2OH C
[0269] Synthesis Example 27 (Surfactant D: containing fluoroalkyl, oxyethylene and hydroxyl groups)
[0270] In a 200 mL flask equipped with a stirrer and a Dean-Stark collector, 26.4 g (0.1 mol) of 1H,1H,2H,2H-nonafluoro-1-hexanol, 6.7 g (0.05 mol) of malic acid (manufactured by Tokyo Chemical Industry Co., Ltd.), 5.0 g of concentrated sulfuric acid, and 100 mL of toluene were added. The mixture was heated to reflux until the theoretical amount of water (1.8 g) could be removed. After cooling to 60 °C, 4 g of quicklime was added, and the mixture was stirred at the same temperature for 30 minutes. After filtration and separation, the toluene was removed by vacuum distillation, thereby obtaining the diester [di-(1H,1H,2H,2H-nonafluoro-1-hexyl) malate] as a yellow, transparent, viscous liquid.
[0271] In a 200 mL flask equipped with a stirrer and a dropping funnel, 19.3 g (0.1 mol) of 28% sodium methoxide methanol solution was added dropwise to a mixture of 31.3 g (0.1 mol) of the obtained diester and 16.9 g (0.1 mol) of 2-(2-(2-chloroethoxy)ethoxy)ethanol at room temperature. The mixture was then heated and stirred at 80 °C for 5 hours. After the reaction was complete, 300 mL of ethyl acetate was added, and the organic layer was washed three times with 150 mL of 20% saline solution. After drying with 30.0 g of anhydrous magnesium sulfate, the solvent was removed by vacuum distillation, thereby obtaining compound D.
[0272] [Chemistry 33]
[0273]
[0274] Synthesis Example 28 (Surfactant E: Contains fluoroalkyl and carboxyl groups)
[0275] In a 1L flask equipped with a stirrer, reflux condenser, and dropping funnel, 57.4 g (0.1 mol) of 1H,1H,2H,2H-heptadecylfluorodecyl iodide (manufactured by Tokyo Chemical Industry Co., Ltd.), 27.6 g of anhydrous potassium carbonate, and 400 ml of acetone were added and mixed. Then, 16.0 g (0.12 mol) of ethyl 2-mercaptopropionate (manufactured by Tokyo Chemical Industry Co., Ltd.) was added dropwise over 10 minutes, and the mixture was stirred at room temperature for 5 hours to allow the reaction to proceed. The resulting reaction mixture was filtered, and the acetone was removed by distillation. The reactants were then removed by vacuum distillation to obtain ethyl 1H,1H,2H,2H-heptadecylfluorodecylmercaptopropionate.
[0276] In a 300 mL flask equipped with a stirrer, reflux condenser, and thermometer, 22.0 g (0.38 mol) of the obtained ethyl 1H,1H,2H,2H-heptadecyl mercaptopropionate, 1.35 g of lithium hydroxide, and 50 mL of water were added. The mixture was stirred at 80 °C for 4 hours to allow the reaction to proceed. After preparing the reaction solution to acidity using hydrochloric acid of specification 1, 300 mL of ethyl acetate was added, and the organic layer was extracted. The extracted organic layer was washed three times with 150 mL of 20% saline solution. After drying with 30.0 g of anhydrous magnesium sulfate, the solvent was removed by vacuum distillation, thereby obtaining compound E.
[0277] [Chemistry 34]
[0278]
[0279] Synthesis Example 29 (Surfactant F: containing fluoroalkyl and sulfonate structures)
[0280] In a 2L flask equipped with a stirrer, reflux condenser, and thermometer, 480.2 g (1 mol) of 3,3,4,4,5,5,6,6,7,7,8,8,9,9,10,10,10-heptadecanethiol (manufactured by Sigma Aldrich) and 149.8 g (1.1 mol) of 1,4-butanesulfonyl lactone (manufactured by Tokyo Chemical Industry Co., Ltd.) were added. The mixture was stirred at 120°C for 4 hours under nitrogen. Then, the mixture was cooled to 25°C, and 460 g of a 10% (w / w) aqueous solution of lithium hydroxide was added. After stirring at 25°C for 30 minutes, the water was removed by distillation under reduced pressure. The obtained compound was recrystallized from methanol to give compound F.
[0281] [Chemistry 35]
[0282] C8F 17CH2CH2-S-C4H9-SO3Li F
[0283] Synthesis Example 30 (Surfactant G: containing fluoroalkyl, oxidized amino, and hydroxyl groups)
[0284] In a 100 mL flask, 47.6 g (0.1 mol) of 1,2-epoxy-1H,1H,2H,3H,3H-heptadecylfluoroundecane (manufactured by Fujifilm Wako Chemical Co., Ltd.) and 20.4 g (0.2 mol) of dimethylaminopropylamine (manufactured by Tokyo Chemical Industry Co., Ltd.) were added, the mixture was heated to 60 °C and allowed to react, and then allowed to mature for 16 hours. Subsequently, the excess amine was removed by distillation at 80 °C under vacuum to obtain 55.8 g of the following compound.
[0285] [Chemistry 36]
[0286]
[0287] In a 100 mL flask, 9.79 g (0.0169 mol) of the compound, 35 g of ethanol, and 5 g of deionized water were added, and the temperature was raised to 65 °C. 2.68 g (0.0237 mol) of 30% hydrogen peroxide solution was added dropwise, and the mixture was allowed to mature at the same temperature for 4 hours to obtain compound G.
[0288] [Chemistry 37]
[0289]
[0290] Synthesis Example 31 (Surfactant H: Silicone Compound)
[0291] In a 1L flask containing a stirrer, reflux condenser, dropping funnel, thermometer, and nitrogen inlet, 100g of cyclohexanone was added, and the mixture was heated to 110°C under nitrogen atmosphere. Maintaining the temperature of the cyclohexanone at 110°C, a monomer solution was prepared by adding dropwise over a dropping funnel at a constant rate for 2 hours to a mixture of 90g (0.91 mol) of N,N-dimethylacrylamide (manufactured by Tokyo Chemical Industry Co., Ltd.), 10g (0.01 mol) of Silaplane FM-0711 (manufactured by JNC Corporation), 1g of tert-butyl peroxide-2-ethylhexanoate, 2g of dodecyl mercaptan, and 200g of cyclohexanone. After the addition was complete, the monomer solution was heated to 115°C and reacted for 2 hours to synthesize a copolymer, thereby obtaining compound H.
[0292] [Chemistry 38]
[0293]
[0294] Synthesis Example 32 (Surfactant I: Acrylic Compound)
[0295] In a 1L flask containing a stirrer, reflux condenser, dropping funnel, thermometer, and nitrogen inlet, 100g of octanol was added, and the mixture was heated to 100°C under nitrogen atmosphere. Maintaining the octanol temperature at 100°C, a mixture of 180g (0.96 mol) of ethoxydiethylene glycol acrylate (manufactured by Tokyo Chemical Industry Co., Ltd.), 120g (0.65 mol) of 2-ethylhexyl acrylate (manufactured by Tokyo Chemical Industry Co., Ltd.), 1g of tert-butyl peroxide, and 100g of octanol was added dropwise over a dropping funnel at a constant rate for 2 hours to synthesize a monomer solution. After the addition was complete, the monomer solution was heated to 115°C, and the reaction was allowed to proceed for 2 hours to synthesize a copolymer. The copolymer was then diluted with octanol to make the remaining amount 50%, yielding compound I.
[0296] [Chemistry 39]
[0297]
[0298] Synthesis Example 33 (Surfactant J: Propylene oxide compound)
[0299] In a 3L flask equipped with a stirring blade, nitrogen purging pipe, thermocouple, cooling pipe, and oil-water separator, 700g of xylitol (manufactured by Tokyo Chemical Industry Co., Ltd.), 1291g of 2,2-dimethoxypropane (manufactured by Tokyo Chemical Industry Co., Ltd.), and 27mg of p-toluenesulfonic acid monohydrate were added. The reaction system was maintained at 60°C–90°C for 2 hours. After the reaction was completed, the byproduct methanol and excess 2,2-dimethoxypropane were removed to obtain the following compound.
[0300] [Chemistry 40]
[0301]
[0302] 235 g of the compound and 15.5 g of potassium hydroxide were added to an autoclave. After replacing the air in the autoclave with dry nitrogen, the catalyst was completely dissolved at 140°C while stirring. Next, 2900 g of butylene oxide (manufactured by Tokyo Chemical Industry Co., Ltd.) was added dropwise using a dropping device, and the mixture was stirred for 2 hours. Then, the reaction product was removed from the autoclave and neutralized with hydrochloric acid to a pH of 6-7. To remove the water content, the mixture was subjected to reduced pressure treatment at 100°C for 1 hour. Finally, the mixture was filtered to remove salts, thereby obtaining the following compound.
[0303] [Chemistry 41]
[0304]
[0305] In a 1L flask equipped with a stirring blade, nitrogen purging pipe, thermocouple, and cooling pipe, 700g of the compound, 70g of water, and 10g of 36% hydrochloric acid were added. The mixture was subjected to a deketalizing reaction at 80°C for 2 hours under sealed conditions. Water and acetone were then removed by external distillation using nitrogen bubbling. The pH was then adjusted to 6-7 using a 10% potassium hydroxide aqueous solution. To remove any remaining water, the mixture was subjected to reduced pressure treatment at 100°C for 1 hour. Finally, the mixture was filtered to remove any salts generated during the treatment, yielding compound J.
[0306] [Chemistry 42]
[0307]
[0308] Examples 1 to 40, Comparative Examples 1 to 16
[0309] The evaluation shall be conducted in the following order.
[0310] (1) Production of nonwoven fabric and observation during spinning
[0311] In each synthesis example, 20 g of a polymer solution with a resin concentration of 35% by mass was mixed with 0.47 g of surfactant to obtain the compositions shown in Tables 1 to 3. The mixture was then diluted using the same solvent as the polymer solution to prepare a composition with a resin concentration of 30% by mass. The prepared compositions are shown in Tables 1 to 3.
[0312] The resin solution was sprayed onto aluminum foil at a rate of 5 g / m² using an electric field spinning device (manufactured by Katotech, Inc., NEU nanofiber electronic spinning unit) at a rate of 40 μL / min. 2 The nonwoven fabric was formed using a method described above. The nozzle used an 18-gauge (0.94mm inner diameter) needle without bevels, and the distance to the collector was set to 15cm. When setting the voltage, for each sample, the nozzle tip was visually checked to ensure the resin solution maintained a stable conical (Taylor cone) shape at the nozzle tip. The nonwoven fabric on the obtained aluminum foil was vacuum dried at 150°C to remove residual solvent.
[0313] The whitening of the filaments during electric field spinning was confirmed by visual observation, and those without whitening were considered acceptable. The results are shown in Tables 1 to 3.
[0314] (2) Observation of non-woven fabrics
[0315] The nonwoven fabric obtained by electric field spinning was observed using a scanning electron microscope (SEM). The accelerating voltage was set to 5 kV and the magnification to 2000x. Observation confirmed that the nonwoven fabric was not piled up in droplets but in a fibrous manner within the field of view; nonwoven fabric with a fibrous pile was considered acceptable. Furthermore, the number of beads was measured, and less than 50 beads were considered acceptable.
[0316] Regarding the composition prepared in (1), after being left at room temperature for 1 month, nonwoven fabric was made again using the method described in (1), and the number of beads was measured in the same way. The results are shown in Tables 1 to 3.
[0317] (3) Measurement of fiber diameter
[0318] Gold sputtered onto nonwoven fabrics obtained by electric field spinning was observed using a scanning electron microscope (SEM). The accelerating voltage was set to 5 kV, the magnification to 10,000x, and 30 fibers within the field of view were randomly selected. The widths of these fibers were measured, and their arithmetic mean was calculated as the fiber diameter. The results are shown in Tables 1-3.
[0319] (4) Method for determining the tensile strength of nonwoven fabrics
[0320] In Examples 3, 7, 13-15, 18, 21, 23, 25, 28, 32, and 35, and Comparative Examples 1, 3, 5, 7, 9, 11, 13, and 15, the strength of the nonwoven fabric was measured. Furthermore, regarding Examples 2 and 6, since a precursor polymer solution was included, an inert oven (CLH-21CD-S; manufactured by KoyoThermo Systems, Ltd.) was used. The temperature was increased to 280°C at 5°C / min with an oxygen concentration below 20 ppm, and the nonwoven fabric was heat-treated at 280°C for 1 hour. Then, it was cooled to 50°C at 5°C / min, and the following measurements were performed.
[0321] Using the same method as (1), the nonwoven fabric from the aluminum foil was separated until the residual solvent was removed (for Examples 3 and 7, this was followed by heat treatment), and the thickness was measured using a micrometer. The electric field spinning time was adjusted to produce a nonwoven fabric with a thickness of 20 μm.
[0322] The nonwoven fabric was cut into strips approximately 1 cm wide and 5 cm long, and the resulting nonwoven fabric was used as a sample for strength testing. Tensile strength was measured using a Tensilon (RTM-100; manufactured by Orientec) instrument, and the average of the first five measured values was taken as the tensile strength. The results are shown in Tables 1 to 3.
[0323] <Tension Strength Test Conditions>
[0324] Temperature: 23℃
[0325] Humidity: 45% RH
[0326] Full-scale load: 25N
[0327] Crosshead speed: 50mm / min
[0328] Fracture detection sensitivity: 1.0%.
[0329] (5) Determination of the 5% weight loss temperature of the resin
[0330] The polymer solutions of Synthesis Examples 1 to 23 were spin-coated onto an 8-inch silicon wafer, and then baked at 120°C for 3 minutes using a hot plate (Coating and Developing Apparatus Act-8; manufactured by Tokyo Electron, Ltd.) to obtain a resin film.
[0331] For the resin membrane, an inert oven (CLH-21CD-S; manufactured by Koyo ThermoSystems, Inc.) was used, with an oxygen concentration below 20 ppm.
[0332] In the cases of (A) Synthetic Examples 2, 4, 8, 10 to 13, and 17,
[0333] The temperature was increased to 280°C at a rate of 5°C / minute, and then subjected to heat treatment at 280°C for 1 hour.
[0334] In the cases of (B) Synthetic Examples 3, 5, 6, 7, 9, 14 to 16, and 18 to 23,
[0335] Heat to 150°C at a rate of 5°C / minute, and perform heat treatment at 150°C for 1 hour.
[0336] Then, it is cooled to 50°C at a rate of 5°C / min. Next, it is immersed in hydrofluoric acid for 1 to 4 minutes, then peeled off from the substrate and air-dried to obtain the heat-treated film. The spin coating speed is adjusted so that the resin film thickness after heat treatment is 10 μm. The film thickness at this point is measured using an optical interferometry film thickness measuring device (Lambda Ace STM-602; manufactured by Dai Nippon Screen Manufacturing Co., Ltd.).
[0337] The membrane was placed in a thermogravimetric analyzer (TGA-50; manufactured by Shimadzu Corporation), heated to 150°C at a heating rate of 10°C / min, and the adsorbed water was removed. It was then temporarily cooled to room temperature, and the weight W1 was measured. When the resin was heated again at a heating rate of 10°C / min, the temperature at which the weight W2 of the resin during the heating process became W2 / W1 = 0.95 was set as the 5% weight reduction temperature. The results are shown in Table 4.
[0338]
[0339]
[0340]
[0341] [Table 4]
[0342]
Claims
1. A resin composition for forming a nonwoven fabric by electric field spinning, said resin composition comprising: (a) a component, at least one heat-resistant resin or a precursor thereof selected from the group consisting of heat-resistant resins containing nitrogen atoms and heat-resistant resins having a group selected from the group consisting of ether groups, ketone groups, sulfone groups and thioether groups in the main chain; (b) a solvent; and (c) a surfactant having a fluoroalkyl group containing a perfluoro group of 4 to 8 carbon atoms, satisfying conditions 1 and 2: Condition 1: It has at least one base selected from the bases represented by general formula (11) and general formula (12). Where n⁴ represents an integer between 2 and 11, and n⁵ represents an integer between 2 and 11. Condition 2: Possesses a hydroxyl group.
2. The resin composition according to claim 1, wherein (c) the surfactant having a fluoroalkyl group does not have a structure formed by repeating units containing a fluoroalkyl group linked together.
3. The resin composition according to claim 1 or 2, wherein the heat-resistant resin of component (a) is a resin selected from the group consisting of polyimide, polyamide-imide, polyamide, polybenzoxazole, polybenzothiazole, polybenzimidazole, polyurea, polyetherketone, polyetheretherketone, polyethersulfone, and polyphenylene sulfide.
4. The resin composition according to claim 1 or 2, wherein the heat-resistant resin of component (a) has a structure represented by at least one of the following general formulas (1) to (5); In general formula (1), R 1 R represents a divalent group with 2 to 50 carbon atoms; 2 m1 represents a tetravalent group with 4 to 50 carbon atoms; m1 represents an integer from 1 to 10000. In general formula (2), R 3 R represents a divalent group with 2 to 50 carbon atoms; 4 m1 represents trivalent groups with 4 to 50 carbon atoms; m2 represents integers from 1 to 10000. In general formula (3), R 5 R represents a divalent group with 2 to 50 carbon atoms; 6 m3 represents divalent groups with 2 to 50 carbon atoms; m3 represents integers from 1 to 10000. In general formula (4), R 7 R represents a divalent group with 2 to 50 carbon atoms; 8 m4 represents divalent groups with carbon numbers from 2 to 50; m4 represents integers from 1 to 10000. In general formula (5), R 9 R represents a divalent group with 2 to 50 carbon atoms; 10 The symbol represents a tetravalent group with 4 to 50 carbon atoms; X represents a divalent group selected from -O-, -S-, -NH- and -C(=O)O-; m5 represents an integer from 1 to 10000.
5. The resin composition according to claim 4, wherein R in general formula (1) 1 R in general formula (2) 3 R in general formula (3) 5 R in general formula (3) 6 R in general formula (4) 7 R in general formula (4) 8 and R in general formula (5) 9 These, at least 30 mol%, have the structure represented by the following general formula (6) or general formula (7); In general formula (6), R 11 n1 represents a monovalent group with carbon numbers 1 to 6, located adjacent to the polymer backbone; n1 represents an integer from 1 to 4. In general formula (7), R 12 and R 13 Each of the following groups independently represents a monovalent group having 1 to 6 carbon atoms, located in an adjacent position relative to the polymer backbone; n2 and n3 independently represent integers 1 to 4; X2 represents at least one selected from single bond, -O-, -S-, -CH2-, -C(CH3)2-, and -C(CF3)2-.
6. A nonwoven fabric comprising: (a) a component selected from a heat-resistant resin containing a nitrogen atom and a heat-resistant resin having a group selected from the group consisting of ether groups, ketone groups, sulfone groups and thioether groups in its main chain; and (c) a surfactant having a fluoroalkyl group containing 4 to 8 perfluoro groups, satisfying conditions 1 and 2: Condition 1: It has at least one base selected from the bases represented by general formula (11) and general formula (12). Where n⁴ represents an integer between 2 and 11, and n⁵ represents an integer between 2 and 11. Condition 2: Possesses a hydroxyl group.
7. The nonwoven fabric according to claim 6, wherein (c) the surfactant having a fluoroalkyl group does not have a structure formed by repeating units containing a fluoroalkyl group linked together.
8. The nonwoven fabric according to claim 6 or 7, wherein the heat-resistant resin of component (a) is a resin selected from the group consisting of polyimide, polyamide-imide, polyamide, polybenzoxazole, polybenzothiazole, polybenzimidazole, polyurea, polyetherketone, polyetheretherketone, polyethersulfone and polyphenylene sulfide.
9. The nonwoven fabric according to claim 6 or 7, wherein the heat-resistant resin of component (a) has a structure represented by at least one of the following general formulas (1) to (5); In general formula (1), R 1 R represents a divalent group with 2 to 50 carbon atoms; 2 m1 represents a tetravalent group with 4 to 50 carbon atoms; m1 represents an integer from 1 to 10000. In general formula (2), R 3 R represents a divalent group with 2 to 50 carbon atoms; 4 m1 represents trivalent groups with 4 to 50 carbon atoms; m2 represents integers from 1 to 10000. In general formula (3), R 5 R represents a divalent group with 2 to 50 carbon atoms; 6 m3 represents divalent groups with 2 to 50 carbon atoms; m3 represents integers from 1 to 10000. In general formula (4), R 7 R represents a divalent group with 2 to 50 carbon atoms; 8 m4 represents divalent groups with carbon numbers from 2 to 50; m4 represents integers from 1 to 10000. In general formula (5), R 9 R represents a divalent group with 2 to 50 carbon atoms; 10 The symbol represents a tetravalent group with 4 to 50 carbon atoms; X represents a divalent group selected from -O-, -S-, -NH- and -C(=O)O-; m5 represents an integer from 1 to 10000.
10. The nonwoven fabric according to claim 9, wherein R in general formula (1) 1 R in general formula (2) 3 R in general formula (3) 5 R in general formula (3) 6 R in general formula (4) 7 R in general formula (4) 8 and R in general formula (5) 9 These, at least 30 mol%, have the structure represented by the following general formula (6) or general formula (7); In general formula (6), R 11 n1 represents a monovalent group with carbon numbers 1 to 6, located adjacent to the polymer backbone; n1 represents an integer from 1 to 4. In general formula (7), R 12 and R 13 Each of the following groups independently represents a monovalent group having 1 to 6 carbon atoms, located in an adjacent position relative to the polymer backbone; n2 and n3 independently represent integers 1 to 4; X2 represents at least one selected from single bond, -O-, -S-, -CH2-, -C(CH3)2-, and -C(CF3)2-.
11. A method for manufacturing a nonwoven fabric, comprising forming a nonwoven fabric by using a resin composition as described in any one of claims 1 to 5 and subjecting it to electric field spinning.
12. A fiber article comprising a nonwoven fabric as claimed in any one of claims 6 to 10.
13. A separator for an energy storage element, comprising a nonwoven fabric as described in any one of claims 6 to 10.
14. A secondary battery having a separator as described in claim 13.
15. An electric double-layer capacitor having a separator as described in claim 13.
Citation Information
Patent Citations
Polyimide fiber, polyimide nonwoven fabric obtained from the same and method for producing them
JP2011132611A
Polyimide fiber, polyimide nonwoven fabric, heat insulation material, electromagnetic wave shield sheet and separator for battery
JP2012251287A
Polyimide fiber mass, sound absorbing material, heat insulation material, flame-retardant mat, filter cloth, heat-resistant clothing, nonwoven fabric, heat insulation / sound absorbing material for aircraft, and heat-resistant bag filter
WO2009054349A1
Resin, resin composition, nonwoven fabric using same, fiber product, separator, secondary battery, and method for producing electric double layer capacitor and nonwoven fabric
WO2019009037A1
Resin, resin composition, nonwoven fabric using same, fiber product, separator, secondary battery, and method for producing electric double layer capacitor and nonwoven fabric
CN110799559A